2018
DOI: 10.4103/0366-6999.240817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Regulatory Network of Exosomes and microRNAs on Neurodegenerative Diseases

Abstract: Objective:A comprehensive review of the network regulation of exosomes and microRNAs (miRNAs) in neurodegenerative diseases was done, centering on the mechanism of the formation of exosomes and miRNAs and the sorting mechanism of exosomal miRNAs, with the aim to provide a theoretical basis in the search of biomarkers and the treatment of neurodegenerative diseases.Data Sources:The comprehensive search used online literature databases including NCBI PubMed, Web of Science, Google Scholar, and Baidu Scholar.Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 103 publications
0
28
0
Order By: Relevance
“…Earlier research has indicated miRNAs as promising biomarkers for treatment of neurodegenerative diseases, including PD, through addressing central nervous system homeostasis. 13 miR-212, as a novel miRNA, has been suggested to be necessary for the development and function of neurons. 14 Moreover, miR-212 is reported to be expressed in cerebrospinal uid in PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research has indicated miRNAs as promising biomarkers for treatment of neurodegenerative diseases, including PD, through addressing central nervous system homeostasis. 13 miR-212, as a novel miRNA, has been suggested to be necessary for the development and function of neurons. 14 Moreover, miR-212 is reported to be expressed in cerebrospinal uid in PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomal miRNAs can transport epigenetic information, affecting gene expression in a recipient cell [41]. Many studies have demonstrated that exosomal miRNAs can play important roles in treatment or detected markers of many diseases, including cancer progression and metastasis [42,43], neurodegenerative diseases [44][45][46], and inflammation [47], and they also participate in the pathological of depression [48,49]. Furthermore, mesenchymal stem cell-derived exosomal miR26a can improve symptoms of depression in rats [50].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are notoriously involved in PD pathogenesis, and can be packaged in exosomes. Exosomes and miRNAs form a network that, both individually and synergistically, participates in the pathogenesis of PD among several other diseases (Mirzaei et al, 2017;Li et al, 2018;Saeedi Borujeni et al, 2018;Pourhanifeh et al, 2019).…”
Section: Micrornas In Exosomes Involved In Pd Pathogenesismentioning
confidence: 99%